Molecular heterogeneity of methicillin-resistant staphylocococcus aureus isolated from humans, animals and environmental surfaces - Woldegiorgis, Erkihun Aklilu (2010)
Methicillin-resistant Staphylococcus aureus (MRSA) has long been known to cause nosocomial infections worldwide since its emergence in the early 1960s. Nowadays, this organism is found to prevail in the wider community and is becoming an emerging problem in veterinary medicine. This study aimed to determine the molecular heterogeneity of the MRSA isolates obtained from human, pets (cats and dogs), and the environment. Swab samples were collected from 103 veterinary medicine students, 28 University Veterinary Hospital (UVH) staff, 100 pets (50 cats and 50 dogs), and 200 environmental surfaces. Conventional biochemical tests, Staphytect Plus® identification kit, growth on selective media, antibiotic sensitivity test (AST), and minimum inhibitory concentration (MIC) determination were used for phenotypic identification while mecA gene detection was used for genotypic detection of MRSA. A total of 43 MRSA were successfully isolated from the different sources. Prevalence rates were 23.3% (24/103), 7.14 (2/28), 8.0% [(8/100), 6.0% (5/50) cats and 10.0% (5/50) dogs], 4.5% (9/200) in students, UVH staff, pets and environment respectively. All MRSA isolates were found to be resistant to three or more antimicrobial agents. The oxacillin MICs ranged from 1.5 μg/mL to ≥256 μg/mL with the majority (86.0%), having MICs of ≥ 4 μg/mL. The mecA gene was found to be present in 83.7% (36/43) of the isolates. Although mecA gene amplification has been accepted as the gold standard for MRSA detection, several other factors are known to confer S. aureus resistance against methicillin. Molecular fingerprinting by pulsed-field gel electrophoresis (PFGE) classified the isolates into three clusters with 26 pulsotypes and three subtypes. Few isolates from the same source category shared similar or close relationship with each other. However, the finger print patterns for the isolates among the different source categories appeared to be too heterogeneous and sporadic. The multi locus sequencing typing (MLST) analyses grouped the selected 10 isolates (5 from human, 3 from pets, and 2 from environmental) into 5 clonal complexes (CCs) and two singletons comprising nine sequence types (STs). Two STs, ST59 and ST5 were previously reported from neighboring countries such as Singapore and Thailand indicating a regional spread of the clones with the potential contribution of human movement. Staphylococcal protein A gene (spa) sequence typing revealed nine distinct spa types including one new spa type (t5697). Combinations of MLST and spa typing methods have revealed the molecular heterogeneity within and in between most of the tested MRSA isolates. The molecular fingerprints of the isolates revealed similarities between human and pets and human and the environment and these are suggestive of the inter-transmission and spread of the MRSA clones from one of the sources to the other. Since there is no database on the molecular fingerprints of MRSA isolates in the country, the findings from this study serve as a baseline data for future studies and to design comprehensive and contextual control strategies to contain further spread of MRSA.